2018
DOI: 10.1101/501189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS) induces increased epidermal green autofluorescence of mouse

Abstract: Our recent studies have suggested that characteristic 'Pattern of Autofluorescence (AF)' of each disease could be a novel biomarker for non-invasive diagnosis of multiple major diseases such as acute ischemic stroke. It is necessary to determine if increased epidermal green AF may be produced by major pathological factors such as inflammation. In our current study, we used C57BL/6Slac mice exposed to LPS to test our hypothesis that inflammation may induce increased epidermal green AF: LPS rapidly induced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Therefore, our current finding that elder men have higher green AF intensity than elder women is consistent with the findings indicating that female have significantly lower risk to develop multiple cardiovascular diseases (7). Our studies have indicated that the green AF intensity is not only highly correlated with the risk to develop multiple cardiovascular diseases, but also a hallmark of tissue injury induced by oxidative stress or inflammation (10,11,19). Therefore, our study has suggested that compared with older female population, the older male population has higher injury levels in their cardiovascular systems.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, our current finding that elder men have higher green AF intensity than elder women is consistent with the findings indicating that female have significantly lower risk to develop multiple cardiovascular diseases (7). Our studies have indicated that the green AF intensity is not only highly correlated with the risk to develop multiple cardiovascular diseases, but also a hallmark of tissue injury induced by oxidative stress or inflammation (10,11,19). Therefore, our study has suggested that compared with older female population, the older male population has higher injury levels in their cardiovascular systems.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that older women do not have decreased serum concentrations of IL-10, an anti-inflammatory cytokine, as older men do (1), which has implicated that older men may have higher levels of inflammation than older women. Since our previous study has suggested that inflammation can induce increased skin's green AF intensity (19), the higher green AF intensity of older men's skin may be caused by their higher levels of inflammation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since oxidative stress can lead to increased epidermal green AF by altering keratin 1 (12,13), the increased oxidative stress of AIS patients (2,6,23) and MI patients (1,5,11,15,24) may be responsible for the increased AF intensity. Our latest study has also indicated that inflammation can produced increased epidermal green AF intensity (26).…”
Section: Introductionmentioning
confidence: 90%
“…Our recent study has suggested that oxidative stress is an important factor that can increase the epidermal green AF by altering keratin 1 (4,5). Our latest study has also indicated that inflammation can induce increased green AF of mouse's skin (15).…”
Section: Introductionmentioning
confidence: 87%